A bioeconomic and general equilibrium framework to address fishery management and invasive species - Apriesnig, Jenny L., author; Goemans, Christopher, advisor; Warziniack, Travis, advisor; Manning, Dale, committee member; Thilmany, Dawn, committee member; Johnson, Brett, committee member (Colorado State University. Libraries, 2017)
Fisheries management is a complex issue that involves the management of people, fish populations and habitat. There are many facets to fishery issues including ownership, regulation, and environmental change. I address all three of these facets in the following work. I develop a general equilibrium model that incorporates fish stock and present two applications of it. I evaluate the change of a fishery under a regulated open access regime to an individual transferrable quota system. I apply the model to the Lake Erie yellow perch fishery, and I account for the different allocations of the value provided by the fish stock, and the potential changes in efficiency. I find that the change to an individual transferrable quota system results in welfare improvements but only if the individual transferrable quota system induces improved catchability and efficiency in fishery effort choices. I also develop an integrated bioeconomic model with the general equilibrium framework to evaluate the joint responses of a regional economy and lake food web to an environmental shock. The model is unique in that there are feedbacks between the economy and food web. The bioeconomic model is used to evaluate a potential Lake Erie Asian carp invasion. There are two primary results from the analysis; the Asian carp invasion leads to welfare improvements, and when invasion impacts are estimated with only the ecological food web model, without the consideration of changes in human choice, the impacts to some fish populations are overestimated while others are underestimated. In both applications, I show that using a general equilibrium framework captures welfare impacts that would be missed by a partial equilibrium analysis.